Analisis Penerapan Akad Murabahah dalam Pembiayaan Konsumtif di Bank Syariah - Hasan, Adnan; Majid, Jamaluddin (Al Rikaz: Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the implementation of the murabahah contract in consumer financing at Bank Syariah Indonesia (BSI) by examining its compliance with PSAK 102, transparency of margins, and the determining factors affecting financing performance and risk. Using a qualitative descriptive-analytical approach, the research collected data through in-depth interviews, observations, and document analysis involving financing officers, customers, and members of the Sharia Supervisory Board (DPS). The findings reveal that the implementation of murabahah at BSI generally complies with the formal requirements of PSAK 102; however, a gap remains between administrative compliance (compliance by design) and substantive transparency (compliance by evidence), particularly in documenting cost prices, margins, and disclosure of payment terms. Furthermore, bank-specific factors such as the Financing to Deposit Ratio (FDR), Third Party Funds (DPK), Non-Performing Financing (NPF), and operational efficiency significantly influence the growth and quality of murabahah financing. The study also finds that customers’ perception of fairness in margin determination and the supervisory role of the DPS are critical in fostering public trust and maintaining the stability of the Islamic financial system. The research implies that strengthening evidence-based PSAK 102 implementation, enhancing Islamic corporate governance, and improving Islamic financial literacy are essential to promote transparency, fairness, and sustainability in murabahah-based consumer financing in Indonesia